Using Statistical Analysis Approach to Evaluate the Groundwater Quality in Jisser Diyala Area - Ramadhan, Ahmad A; Hussian, Tariq A; Nada, Kamal B (Al-Nahrain Journal of Science, 2017)
Multivariable statistical approach were applied to evaluate groundwater quality in Jisser Diyala area, this technique was used to find the relation between physco-chemical properties of water and pattern of changing the groundwater quality in this area. Cluster and Factor analysis were applied in two type R-mode and Q-mode to identify the grouping of chemical properties and identify the factors controlling the change in quality